2001
DOI: 10.1159/000050861
|View full text |Cite
|
Sign up to set email alerts
|

Les amétropies statiques du noir camerounais

Abstract: Purpose: We undertook this study with the aim to determine static ametropias of black Cameroonians as well as their clinical manifestations. It is a prospective study carried out in the Department of Ophthalmology of Douala General Hospital from January 1996 to December 1998. Patients and Method: During this period, all patients who fulfilled our criteria had a skiascopy done under cycloplegia. We thus examined 2,484 patients (4,968 eyes). 66.2% of them were female and 33.8% were male. Results: In our series, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 2 publications
3
7
0
1
Order By: Relevance
“…Taking into account the spherical equivalent of different ametropia, 79.57% of our patients had hyperopia between 0.25 and 2.5 diopters (Table 3), which is consistent with Ebana [12] results in Cameroon, where hyperopia and astigmatism hyperopia accounted for 78.5% of patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Taking into account the spherical equivalent of different ametropia, 79.57% of our patients had hyperopia between 0.25 and 2.5 diopters (Table 3), which is consistent with Ebana [12] results in Cameroon, where hyperopia and astigmatism hyperopia accounted for 78.5% of patients.…”
Section: Discussionsupporting
confidence: 90%
“…These results are close to those of Ebana [12] in Cameroon with 4.6% myopia and 51% hyperopia. We had a little more patients with astigmatism because of the use of the auto-refractometer which is a little more sensitive to the detection of astigmatism [7].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found a higher frequency of visual acuity problems among girls than boys. Other authors have reported a higher frequency of hypermetropia among girls [18] [19] or myopia among boys [20]. No physio-pathological explanation could be identified.…”
Section: Discussionmentioning
confidence: 87%
“…Visual complaints are frequent among children with visual acuity impairments. Tearing, ocular itchiness and headaches were described by other authors [10] [11] [21]. Vision problems have a direct impact on academic outcomes.…”
Section: Discussionmentioning
confidence: 93%